2021
DOI: 10.1002/ccd.29831
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus eluting bioresorbable vascular scaffolds in patients with acute coronary syndromes: Two‐year results from the German‐Austrian ABSORB registry

Abstract: Objectives To identify potential differences in 2‐year outcome between patients who underwent coronary revascularization using bioresorbable vascular scafffolds (BVS) in stable coronary artery disease (CAD) and acute coronary syndromes (ACS). Background Data from randomized trials suggest a significantly higher event rate following coronary revascularization using everolimus‐eluting BVS as compared to new generation drug eluting stents. Whether particular patient subgroups are at increased risk for scaffold th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…The incidence of MACE in the EROSION study was 3.6% at 1‐month follow‐up, 7.5% at 1‐year follow‐up, and 23.1% at 4‐year follow‐up. 6 , 7 Previous studies have reported that the incidence of MACE in patients with ACS after stent treatment is 3% to 6% at 1 month, 15 , 16 6% to 9% at 1 year, 15 , 17 11% to 12% at 2 years, 18 , 19 and 13% at 3 years, 20 , 21 which is lower compared with that in the EROSION study, but this is because none of these studies included rehospitalization because of unstable or progressive angina as MACE. The proportion of these patients is 15.5% in our study.…”
Section: Discussionmentioning
confidence: 83%
“…The incidence of MACE in the EROSION study was 3.6% at 1‐month follow‐up, 7.5% at 1‐year follow‐up, and 23.1% at 4‐year follow‐up. 6 , 7 Previous studies have reported that the incidence of MACE in patients with ACS after stent treatment is 3% to 6% at 1 month, 15 , 16 6% to 9% at 1 year, 15 , 17 11% to 12% at 2 years, 18 , 19 and 13% at 3 years, 20 , 21 which is lower compared with that in the EROSION study, but this is because none of these studies included rehospitalization because of unstable or progressive angina as MACE. The proportion of these patients is 15.5% in our study.…”
Section: Discussionmentioning
confidence: 83%